English Teachers' Reflections and Lessons Learned in Language Teaching During COVID-19 Pandemic - Komilie Situmorang; Santa M Pramusita; Dwi Y Nugroho (Universitas Sulawesi Barat, 2021)
This study seeks to find out the English teachers' reflections and lessons learned in language teaching during the pandemic. The method used was a guided narrative frame in which the teachers from the suburban wrote down their feelings and lived experiences. The data was analysed using thematic analysis and presented in themes. The findings indicate that the teachers found it challenging at the beginning of their online teaching. Both the teachers and students faced problems including economic situations, tech problems and mental struggles. Interestingly, this finding is similar to the outskirt teachers and students' problems. Besides, the teachers have learned the most vital things during their language teaching in the early year of the pandemic. They continuously shift their teaching strategies, provide personalised feedback to support the students' engagement, and become adaptable teacher-learners. Suggestions are provided for both teachers and policymakers.